Pension Reform in Bolivia: A Review of Approach and Experience - Federico Escobar; Osvaldo Nina (Institute for Advanced Development Studies (INESAD), 2004)
The paper analyzes the Bolivian experience in switching from an old publicly managed pay-as-you-go pension system to a privately managed, fully funded pension system.
Keywords: H55; 330; Pension reform; Bolivia